Barriers to teaching English for specific purposes (ESP): a case from a private school in Indonesia - Nanda Pambudi; Nurhastuti Devi (IRecall Journal, 2025)
This study investigated teachers' barriers when providing English for Specific Purposes (ESP) instruction to airline staff students at a private high school. The research methodology used in this examination was qualitative, adopting a case study approach. The current study employed a purposive sampling strategy to recruit two English for Specific Purposes (ESP) teachers who instruct Airline Staff in English as participants. The data were gathered through interviews and then evaluated and presented in a descriptive manner using theme analysis. The study unveiled that educators experienced diverse obstacles when instructing English for Specific Purposes (ESP). The problems included: a) the requirement for a proper textbook tailored to the specific discipline, b) the build-up of English language practice among students, and c) the necessity for more vocabulary relevant to their academic field